Real estate and the great crisis: Lessons for macro-prudential policy - John V. Duca; Lilit Popoyan; Susan M. Wachter (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
From a broad macro-financial structure perspective, overly easy credit conditions gave rise to house price booms and busts in several advanced economies (e.g., Ireland, Spain, and the U.S.), and, more specifically in the U.S., an underpricing of risk made possible by regulatory arbitrage and shadow financing fueled the credit and twin real estate bubbles of the mid-2000s. Across countries and over time bubbles have been particularly acute in real estate markets reflecting not only the relatively inelastic supply of land and thin trading of real estate, but also the amplification of shocks via backward-looking price expectations and the funding of consumption off distorted and elevated prices. The macro-prudential lessons from the Great Crisis highlight the need to prevent the build-up of excess real estate financing and limit the amplification and correlation of real estate risks. And progress has been made in each of these areas through imposing tougher or new restrictions on the choice sets of lenders or of borrowers, with particulars varying across advanced economies. While regulatory reform of banking is going forward, significant challenges remain especially in dealing with correlated risks associated with securitization.
Keywords: G28; E3; R31; R33; R38; 330; Macro-prudential policy; financial crises; credit crunches; real estate bubbles; regulatory arbitrage; risk-taking